Case Report: Direct Visualization of the Nervus Intermedius During the Microvascular Decompression Procedure: Should We Take It Seriously? - Zheng, Rui-zhe; Zhao, Chang-yi; Zhao, Zhi-jie; Li, Xin-yuan (Frontiers in Neurology, 2021)
Background: Nervus intermedius neuralgia (NIN), known as geniculate neuralgia (GN), is an uncommon cranial nerve disease caused by an offending vessel compressing the nervus intermedius (NI). Microvascular decompression (MVD) has now become a valued treatment approach for NIN because it can resolve neurovascular conflict (NVC) at the root entry zone of the NI. In the era of continuously optimizing and improving the surgical technique of MVD, further minimization of all possible postoperative complications is not only welcome but also necessary. Objective: The aim of this work is to assess the postoperative outcome of direct visualization of the NI during the MVD procedure. Methods: This study retrospectively reviewed the clinical records of a group of seven consecutive patients with NIN who underwent MVD in the period of 2013–2020 in our clinic and 16 studies reported NIN patients who underwent MVD in the period of 2007–2020. Results: In total, 91.3% of all patients experienced immediate and complete relief of cranial neuralgia after MVD. Six of 23 patients have experienced direct visualization of the NI intraoperatively, and 66.7% of those patients had complications such as facial paralysis, dysacousia, or a combination of these conditions postoperatively. Slight surgical approach-related complications such as complaints associated with excessive drainage of cerebrospinal fluid (CSF), nausea and vertigo, and delayed wound union were observed in 80% of the remaining 15 patients, and these symptoms are totally relieved in the telephone and outpatient follow-up after 6 months. Conclusion: Our case series shows that MVD produced immediate pain relief in the majority of NIN patients. MVD carries surgical risk, especially in patients who experience direct visualization of the NI after mechanical stretch and blunt dissection in surgical procedures. Attempts to avoid mechanical stretch and blunt dissection of the compressed nerve were important for intraoperative neuroprotection, especially facial nerve protection